2011
DOI: 10.1128/iai.01344-10
|View full text |Cite
|
Sign up to set email alerts
|

IglG and IglI of the Francisella Pathogenicity Island Are Important Virulence Determinants of Francisella tularensis LVS

Abstract: The Gram-negative bacterium Francisella tularensis is the causative agent of tularemia, a disease intimately associated with the multiplication of the bacterium within host macrophages. This in turn requires the expression of Francisella pathogenicity island (FPI) genes, believed to encode a type VI secretion system. While the exact functions of many of the components have yet to be revealed, some have been found to contribute to the ability of Francisella to cause systemic infection in mice as well as to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
105
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(120 citation statements)
references
References 79 publications
15
105
0
Order By: Relevance
“…We followed bacterial numbers of the ⌬pdpC, ⌬iglC, ⌬iglG, and ⌬iglI mutants and the LVS strain in J774 cells after infection. In agreement with previously published data (20,(23)(24)(25)(26)(28)(29)(30), the ⌬iglC and ⌬pdpC mutants showed very marginal net replication, whereas the ⌬iglG and the ⌬iglI mutants replicated as well as LVS (Table 1). In separate experiments, we observed that the complemented strains showed the same degree of replication as did LVS (not shown).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…We followed bacterial numbers of the ⌬pdpC, ⌬iglC, ⌬iglG, and ⌬iglI mutants and the LVS strain in J774 cells after infection. In agreement with previously published data (20,(23)(24)(25)(26)(28)(29)(30), the ⌬iglC and ⌬pdpC mutants showed very marginal net replication, whereas the ⌬iglG and the ⌬iglI mutants replicated as well as LVS (Table 1). In separate experiments, we observed that the complemented strains showed the same degree of replication as did LVS (not shown).…”
Section: Resultssupporting
confidence: 82%
“…Examples of such mutants include those of the iglABCD operon and the core components VgrG and DotU (20)(21)(22)(23)(24)(25). In contrast, we have observed that the ⌬iglI and ⌬iglG mutants showed aberrant intracellular replication and very diminished cytopathogenic effects (26). The ⌬pdpC mutant of the LVS and the highly virulent F. tularensis subsp.…”
mentioning
confidence: 64%
See 3 more Smart Citations